2009
DOI: 10.2174/1874387000903010044
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Blood Lactate and Oxidative Stress Biomarkers Following Acute Exercise

Abstract: We measured blood lactate, protein carbonyls (PC), and malondialdehyde (MDA) before and immediately after exercise (graded exercise treadmill test [GXT], Wingate cycle sprint, barbell squat, and barbell bench press) in active men. Data were analyzed using a 4 (exercise mode) x 2 (time) ANOVA with Tukey post hoc testing, and pairwise correlations were made. An interaction was noted for lactate (p = 0.009), with values increasing for all modes, and higher post exercise for bench press compared to Wingate and squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Similarly, our findings showed that plasma concentrations of LDH recorded on P2 are significantly higher than those at P1 in EG and CG. Indeed, the study of Bloomer & Cole () clearly supports an increase in the CK and LDH concentrations in the blood in response to intense exercise.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, our findings showed that plasma concentrations of LDH recorded on P2 are significantly higher than those at P1 in EG and CG. Indeed, the study of Bloomer & Cole () clearly supports an increase in the CK and LDH concentrations in the blood in response to intense exercise.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with previous studies, the evaluation of the antioxidant activity indicate T A B L E 3 Cardiovascular parameters (mean ± SE) measured Before (P1) and After (P2) the YYIRT, before and after supplementation that the Opuntia ficus-indica juice studied contain substances which are able to inhibit the action of free radicals as DPPH • (Maataoui et al, 2006;Tesoriere et al, 2008). The choice of the DPPH • method is in accordance with that of Fernandez-Lopez et al (Bloomer & Cole, 2009).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15 Also obtained through research, increased concentrations of blood lactic acid after exercise between before the bench press exercise. 16 EBF speed will decrease the volume of body fluids, which will accelerate the increase in blood lactic acid concentrations. 17 EBF excess will reduce concentration of O2 in blood so that glycolysis in the liver will decrease and followed by an increase in blood lactic acid concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the findings contradict to results of some previous studies. These contradictions in studies probably indicate that hydrogen peroxidation levels may also be affected by inflammatory markers, some researchers have pointed to the relationship between LDH and free radicals, and it has been reported that increased LDH enzymes have an inhibitory role in increasing of free radicals (Bloomer and Cole, 2014).…”
Section: Discussionmentioning
confidence: 99%